Method validation of delphinidin-3-o-glucoside chloride in rat plasma by High-Performance Liquid Chromatography (HPLC) - Shafawi, Nur Atielah Nabila Mohd (2022)
Hibiscus sabdariffa (Roselle) is one of the enormously explored medicinal plants with high anthocyanin, which is essential in treating various diseases. This study was conducted on the high-performance liquid chromatography (HPLC) method for detecting and quantifying delphinidin-3-o-glucoside chloride, one of the anthocyanins present in Hibiscus sabdariffa in the rat plasma. In addition, the HPLC method was validated following the solid-phase extraction method to demonstrate that this analytical method is suitable and to assure its reliability of H.sabdariffa pharmacokinetics and bioavailability study in rat plasma. Six validation parameters were assessed according to FDA guidelines: linearity, recovery, precision, accuracy, limit of detection, and limit of quantification. The calibration curve of delphinidin-3-0-glucoside chloride had a coefficient determination (R2) of ≥95.0%. The recovery percentage of delphinidin3-0-glucoside was found to be 80.377%. Delphinidin-3-o-glucoside chloride also showed good precision and accuracy. The method detection and quantification limits for delphinidin-3-o-glucoside chloride were 47ng/mL and 213ng/mL, respectively. In conclusion, the validated HPLC method in this study can be used to determine anthocyanins in the future pharmacokinetic study of roselle.